Bulky hinge bracelet: inspired by (Batik Sarung) / Nur Afiqah Mohd Azrin - Mohd Azrin, Nur Afiqah (2022)
Batik is a traditional textile craft produced using wax-based patterns. The batik used is divided into two type, local and foreign. The new dimension of batik has now changed to jewelry and clothing. Batik ornaments will be found on hand fans, accessories such as money bag.